Coping Strategy Masyarakat di Tengah Pandemi Covid-19 Effect Status Sosial dan Gender: Studi Expost Facto di Jakarta - Suhardin Suhardin (Yayasan Rahmat Islamiyah, 2021)
Humans have immunity and self immunity, biological pain due to viruses against antibodies, psychological pain due to mental pressure is opposed by coping strategies, this is an interesting study. This study aims to determine the level of community coping strategy in the city of Jakarta during the Covid-19 pandemic by looking at the influence of social status and gender. Looking in more detail related to differences in coping strategies in people with high and low social status, differences in coping strategies in high social status societies that are male and female, as well as in low social status societies that are male and female and see the interactions in these four social groups. This study is a quantitative expost facto study with forty-four sampling, twenty-two with high social status, male eleven and female eleven, as well as twenty-two low social status eleven males and eleven females, selected randomized sampling in South Jakarta, representing DKI Jakarta. The results of descriptive analysis and inferential analysis found that there are differences in coping strategies between people with low social status and high social status, at high social status there are differences in male and female coping strategies, as well as in low social status there are differences in male and female coping strategies. and there is an interaction between the four social groups, thus there is an influence of social status and gender on the coping strategy. Position, function, role and individual social status affect coping strategies, strengthening individual coping strategies needs to pay attention to one's social status and gender.Key word: Covid-19, coping strategis, status sosial, gender.